Antimutagenic effects of copaiba oils (Copaifera langsdorffii Desf.) and flaxseed (Linum usitatissimum L.) against the clastogen – cyclophosphamide, in Wistar rat (Research, Society and Development, 2022)
Copaiba oil extracted from the trunk of Copaifera langsdorffii Desf. and flaxseed oil extracted from the seeds of Linum usitatissimum L., are widely used for the prevention and treatment of many diseases, including cancer. The aim of this study was to assess the antimutagenic effect of these oils against the damage-inducing agent cyclophosphamide, in Rattus norvegicus treated in vivo, by gavage, using cytotoxicity and chromosomal alteration test. The animals were submitted to a single dose of copaiba oil and of flaxseed oil in the simultaneous treatment, pre-treatment and pos-treatment for 24 hours. None of these treatments presented cytotoxic effect. Treatments both oils and cyclophosphamide have significantly reduced the chromosomal damage caused by the clastogen. In groups treated with copaiba oil the reduction percentage was 77% for the simultaneous treatment, 83% for the pre-treatment and 75% for the pos-treatment, whereas in those treated with flaxseed oil was 94% for the pre-treatment and 96% for the simultaneous and pos-treatment. These results indicate that the both oils are not mutagenic, in contrast, they present antimutagenic activity against this clastogenic agent, which represents a protective effect on the cells against the drug that has damaged the genetic material.